Ruwatan Bumi as Ethnopedagogy: An Ethnographic Study of Sundanese Local Wisdom in Banceuy Traditional Village - Wendi Nilpa Apriana; Teguh Ibrahim; Ira Rengganis; Deti Lotaningrat; Evi Rahmawati (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to explore how the Ruwatan Bumi ceremony in the Banceuy Traditional Village, Subang - West Java can become a Sundanese Ethnopedagogy system that internalizes the values of Sundanese local wisdom in the younger generation. The research method uses an ethnographic study that focuses on exploring various activities. Data were collected through participant observation, in-depth interviews with community leaders, and documentation of ritual artifacts during the Ruwatan Bumi celebration in 2025. The findings reveal four main themes. First, cross-generational social collectivity at all stages of the activity. Second, spirituality and respect for ancestors in ritual activities represent gratitude, sacrifice, and protection. Third, ecological wisdom and agrarian cosmology reflect the balance between humans, nature, and God. Fourth, cultural transmission through the active participation of the younger generation in ritual practices, dance performances, accompanying music and various attractions can strengthen cultural identity. This study shows that Ruwatan Bumi not only functions as a cultural ritual but also as a Sundanese Ethno Pedagogy system based on Traditional Villages. This study offers insights into how the local wisdom of Sundanese traditional villages can integrate character education, ecological awareness, spiritual development, and cultural sustainability based on Etnhopedagogy framework